The Effect of Annealing on Electrochemical Performances of an Al–Sn–Ga–Mg Alloy as an Anode for Al–air Batteries in Alkaline Electrolytes. Issue 10 (22nd June 2020) - Han, Zhaohui; Xu, Yang; Zhou, Shenggang; Xu, Lei; Zhu, Peixian
Abstract : In this study, an Al-0.08Sn-0.08Ga-0.5Mg alloy was annealed at 200 °C–400 °C for 10 h. The microstructure and corrosion morphology of the Al anode were observed by scanning electron microscopy (SEM), and the effects of different annealing temperatures on the electrochemical properties of the Al anodes were studied by the hydrogen evolution rate, open circuit potential, Tafel curves, EIS and constant current discharge. The results show that the annealing treatment had a certain effect on the number and size of precipitates on the alloy surface, which improved the electrochemical activity and corrosion resistance of the Al alloy. Additionally, the Al–Sn–Ga–Mg alloy anode material has an excellent discharge performance in the actual use process when the annealing temperature is 350 °C, the related performance parameters were greatly improved compared with other annealing temperature conditions. The capacity density is 2670.99 mAh·g −1, and the energy density is 3379.15 mWh·g −1 .